Less Income Inequality and More Growth - Are they Compatible? Part 5. Poverty in OECD Countries - Pisu, Mauro (OECD Economics Department Working Papers, 2012)
Poverty is an important policy issue in OECD countries and the recent crisis has made it even more pressing. This paper highlights poverty rate differences across countries and reviews the various policies to tackle it. The OECD-wide poverty rate has drifted up, reaching around 11% in the late 2000s. In the majority of OECD countries, children suffer from a higher poverty rate than working-age people and poverty is more wide-spread among women than men. Albeit boosting employment is essential to reduce poverty rates durably, work alone does not suffice to eliminate it as in-work poverty is a problem in many countries The redistribution system is effective in reducing poverty. Countries achieving a greater reduction in market-income poverty tend to redistribute more towards people at the bottom of the income distribution. Policies aiming at facilitating paid work along with employment-conditional cash transfers to top-up the income of low-wage workers can offer effective ways to combat poverty. Child poverty is also a major concern because of its adverse long-term effects. Countries with low levels of child poverty combine low levels of joblessness among parents with effective redistribution policies towards children. This suggests these two policy approaches are complementary and relying exclusively on only one of them is likely to be insufficient to reduce poverty among children significantly